A bond-based correspondence model and its application in dynamic plastic fracture analysis for quasi-brittle materials. (June 2021) - Chen, Zhuang; Wan, Ji; Xiu, Chenxi; Chu, Xihua; Guo, Xianyang
Highlights: A bond-based correspondence model is proposed. A displacement gradient of bond is defined. A bond-based correspondence plastic model is developed. The effect of plastic parameters on dynamic crack propagation is investigated. Abstract: This work presents a generalized bond-based peridynamic model named bond-based correspondence model to simulate the fracture. This model combines the advantages of bond-based peridynamics and the correspondence model (non-ordinary state-based peridynamics). The peridynamic pair-wise force is calculated by classical constitutive equations through the relation between peridynamic pair-wise force and stress. With specific function types of relation between peridynamic pair-wise force and stress, the bond-based correspondence model can degenerate to the existing bond-based peridynamic models, such as the extended peridynamic model with bond rotation and the micropolar peridynamics. Besides, this model is easy to be extended to plasticity, in this study, the small deformation von Mises elastoplastic model is developed. And the effects of plastic parameters on dynamic fracture are analyzed for quasi-brittle materials. Numerical examples illustrate the model's capacity in solving the fixed Poisson's ratio and simulating dynamic crack propagation. And the numerical results show that plastic parameters have a great impact on fracture propagation, including crack initiation and the speed of propagation.